Project Method Application in TESL - Tsyntar, Natalia (Scientific and pedagogical internship (Cuiavian University in Wloclawek, 2024)
In modern approaches of teaching foreign languages, the project method is considered one of the most effective ways of organizing the studying process for groups of students. It provides conditions for creative self-realization of students of higher education institutes, increases motivation for studying, promotes the development of intellectual abilities and research skills. The main idea of such an approach of teaching a foreign language is to shift the emphasis from the tedious and monotonous exercises to the active mental activity of students, which requires proficiency in certain linguistic means for its implementation.
Keywords: project method, practical tasks, synthesis, analysis, educational process